Direct‐acting antivirals do not increase the risk of hepatocellular carcinoma recurrence after local‐regional therapy or liver transplant waitlist dropout. Issue 2 (16th May 2018) - Huang, Annsa C.; Mehta, Neil; Dodge, Jennifer L.; Yao, Francis Y.; Terrault, Norah A.
Abstract : Whether direct‐acting antivirals (DAAs) increase the risk of hepatocellular carcinoma (HCC) recurrence after tumor‐directed therapy is controversial. We sought to determine the impact of DAA therapy on HCC recurrence after local‐regional therapy (LRT) and waitlist dropout among liver transplant (LT) candidates with HCC. We performed a retrospective cohort study of 149 LT candidates with hepatitis C virus (HCV) and HCC at a single center from 2014 through 2016. Cumulative incidence of HCC recurrence post‐LRT and waitlist dropout was estimated by the DAA group. Factors associated with each outcome were evaluated using competing risks regression. A propensity score stabilized inverse probability weighting approach was used to account for differences in baseline characteristics between groups. The no DAA group (n = 87) had more severe cirrhosis and lower rates of complete radiologic tumor response after LRT than those treated with DAA (n = 62) but had similar alpha‐fetoprotein and tumor burden at listing. Cumulative incidence of HCC recurrence within 1 year of complete response after LRT was 47.0% in the DAA group and 49.8% in the no DAA group ( P = 0.93). In adjusted competing risk analysis using weighted propensity score modeling, risk of HCC recurrence was similar in the DAA group compared to those without DAA (hazard ratio [HR], 0.91; 95% confidence interval [CI], 0.58‐1.42; P = 0.67). Patients treated with DAAs had lower risk of waitlist dropout due to tumor progression or death compared to the no DAA group in adjusted weighted analysis (HR, 0.30; 95% CI 0.13‐0.69; P = 0.005). Conclusion : In LT candidates with HCV and HCC with initial complete response to LRT, DAA use is not associated with increased risk of HCC recurrence but rather is associated with reduced risk of waitlist dropout due to tumor progression or death. (Hepatology 2018).